2000
DOI: 10.1016/s0928-8244(00)00204-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a matrix metalloproteinase inhibitor on host resistance against Listeria monocytogenes infection

Abstract: Hydroxy acid-based matrix metalloproteinase (MMP) inhibitors have been shown to inhibit tumor infiltration and growth, endotoxin shock, and acute graft-versus-host disease. Blockade of the release of soluble tumor necrosis factor-alpha (TNF-alpha) and CD95 ligand (CD95L; FasL) from cell-associated forms is reportedly involved in the mechanism of the drug effect. We investigated the effect of a MMP inhibitor, KB-R7785, on host resistance against Listeria monocytogenes infection, in which TNF-alpha is essentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…MMP secretion has been more extensively studied in other bacterial infections and it is known that Mycobacterium tuberculosis is able to induce both MMP‐2 and MMP‐9 from murine macrophages [10]. Other infections capable of inducing MMPs include Lyme disease [27], chlamydial infections [28] and Listeria monocytogenes infection [11]. Bacterial products, such as mycobacterial cell walls, lipopolyaccharide and heat‐shock proteins [28–30], have also been shown to increase MMP secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP secretion has been more extensively studied in other bacterial infections and it is known that Mycobacterium tuberculosis is able to induce both MMP‐2 and MMP‐9 from murine macrophages [10]. Other infections capable of inducing MMPs include Lyme disease [27], chlamydial infections [28] and Listeria monocytogenes infection [11]. Bacterial products, such as mycobacterial cell walls, lipopolyaccharide and heat‐shock proteins [28–30], have also been shown to increase MMP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that MMPs are major effector molecules causing tissue damage in ulcerative colitis [6]. Other studies have suggested that MMPs contribute to tissue remodelling processes, and possibly tissue damage, in bacterial infections [10,11]. MMPs can be induced both by bacterial products (e.g.…”
mentioning
confidence: 99%
“…[40][41][42] MDS patients also have deficiencies in the contents of neutrophil granules, including quantitative and/or functional anomalies of myeloperoxidase, lactoferrin and antibiotic proteases such as elastase and cathepsin G, [43][44][45][46] deficiencies in granule membrane glycoproteins, 44 and matrix metalloproteinase dysfunction. [47][48][49] Impaired activity of granule proteases in neutrophils, which can induce tissue injury through an inflammatory-mediated process, is potentially implicated in the increased susceptibility to infections even in the absence of neutropenia. [50][51][52] However, these defects have still not been well defined in clinical studies.…”
Section: Functional Neutrophil Impairmentmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) degrade all extracellular matrix (ECM) components and perform important tasks such as tissue remodeling and modulation of the immune system (39,45). Increased expression of MMPs is known in many central nervous system diseases such as multiple sclerosis, experimental autoimmune encephalomyelitis, alzheimer's disease, stroke and meningitis (38,42).…”
Section: Introductionmentioning
confidence: 99%